Prospective study of uveitis in children with juvenile idiopathic arthritis over a 3-year period. Issue 1 (10th February 2023) - Markova, Malina; Stefanov, Stefan; Teltcharova-Mihaylovska, Albena; Oscar, Alexander
Abstract: Juvenile idiopathic arthritis (JIA) is the most common systemic autoimmune disease in childhood, which can cause non-infectious uveitis. Ocular inflammation is the most severe, sight-threatening extra-articular complication. In this prospective three-year study 81 children with identified autoimmune diseases were observed of whom 56 were with JIA. Uveitis was observed in 21 of the children with JIA. All children were followed up for three years between December 2019 and November 2022 in the Department of Ophthalmology, University Hospital 'Alexandrovska' and the Department of Paediatric Rheumatology, University Children Hospital, Sofia, Bulgaria. Uveitis developed in 21 (37.5%) of 51 children diagnosed with JIA. Systemic immunosuppressive medications were more common among children with uveitis (31[38.27%]), compared to children without uveitis (27 [23.1%]). Ocular complications occurred in 15[26.78%] of the children with JIA. The early onset of uveitis after the diagnosis of JIA was a risk factor for developing ocular complications. Detected antinuclear antibodies (ANA) was also a risk factor for developing uveitis in children with JIA. The median age at the time of diagnosis of uveitis was 3.76 years. Our results support the recommendation that the screening for uveitis should start immediately when arthritis is suspected or confirmed and that all children with JIA should be monitored by an ophthalmologist every three to six months. Systemic immunosuppressive treatment in combination with biological therapy is considered early in the course of the disease in children with a high risk of developing ocular complications.